Smart biomaterial-based systems for intrinsic stimuli-responsive chronic wound management. (December 2021) - Alves, P.M.; Barrias, C.C.; Gomes, P.; Martins, M.C.L.
Abstract: Skin chronic wounds are associated with a state of persistent inflammation and often with infection, originating a specific microenvironment characterized by increased temperature, alkaline pH, elevated enzymatic activity, and high levels of reactive oxygen species (ROS). These alterations can be explored as intrinsic triggers in the design of stimuli-responsive biomaterials for the release of bioactive molecules at the wound microenvironment. Stimuli-responsive biomaterials may not only prolong the bioactivity of the therapeutic agents but also synchronize it with the healing stages, tuning the wound treatment. In addition, the high activity of enzymes, such as lysozyme in infected chronic wounds, as well as the shift to a more alkaline pH may be used as biomarkers for early detection of infected and/or non-healing wounds. Overall, although a few shortcomings still need to be addressed before clinical translation, the bioengineered smart formulations highlighted in this review stand out as a new generation of therapies to manage skin chronic wounds. Graphical abstract: Image 1 Highlights: Chronic wounds have increased pH, temperature and levels of enzymes, and reactive oxygen species. Stimuli-responsive systems allow microenvironment-specific chronic wound treatments. Smart wound monitoring can provide a complete setup for chronic wound management. Some shortcomings in these systems need to be addressed before clinical translation.